Diagnóstico ambiental do município de Boa Esperança (MG) - Marangon, Kaueh Cardoso (Universidade Federal de São Carlos, 2024)
The municipality of Boa Esperança, located in the south of Minas Gerais, was founded in the 19th century during the gold exploration era in the region. With the introduction of coffee cultivation, the municipality became an important producer, with 98% of its territory in 2022 dedicated to grain production for domestic consumption and export. The economic development driven by coffee cultivation allowed for local growth, combined with the damming of waters from the Furnas Hydroelectric Plant, has created opportunities for the consolidation of tourism-related activities, ranging from the hotel industry to hosting international events. The establishment of the Boa Esperança State Park in 2007, justified by the need to preserve remnants of Cerrado and Atlantic Forest, further strengthened the area's tourism potential, significantly influencing the local economy. Consequently, various changes occurred in the municipal territory in terms of land cover and impacts on protected green areas. In this context, the present study aimed to assess the Permanent Preservation Areas in the municipality, which currently have less than 40% forest cover. Other relevant findings point to the direct conversion of native vegetation areas for coffee cultivation and other agricultural uses, the presence and urbanization of economically impactful activities along the shores of Lago dos Encantos, and the development of a Municipal Master Plan that does not account for urban green areas as preservation zones nor considers the potential creation of an urban open space system that would benefit the population.
Environmental diagnosis of the municipality of Boa Esperança (MG)
Keywords: Diagnóstico ambiental; Áreas de preservação permanente; Geoprocessamento; Environmental assessment; Permanent preservation areas; Geoprocessing; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL